1991
DOI: 10.1525/aeq.1991.22.3.05x1050j
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Culturally Based Pedagogy: A Case Study of One Yup'ik Eskimo Teacher

Abstract: This case study is part of an ongoing collaborative research project with Yup'ik teachers in southwest Alaska. On the surface, this lesson appears to be an art lesson, but a cultural interpretation suggests it is about subsistence and survival. Implicit in this case for minority education is the importance of adapting social interactions, knowledge, and values toward the minority culture as one possible means for improving schooling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 20 publications
5
55
0
Order By: Relevance
“…As Lipka (1991) suggested that most academics try to identify with their students in creating a positive learning climate, built on mutual respect and trust. Lipka (1991) continues with the proposal that academics should encourage ethnic minority groups to be critically aware of their own personal experiences and cultural values. One academic commented:…”
Section: Pillar 4: Cultural Bridgingmentioning
confidence: 99%
“…As Lipka (1991) suggested that most academics try to identify with their students in creating a positive learning climate, built on mutual respect and trust. Lipka (1991) continues with the proposal that academics should encourage ethnic minority groups to be critically aware of their own personal experiences and cultural values. One academic commented:…”
Section: Pillar 4: Cultural Bridgingmentioning
confidence: 99%
“…(Lipka, 1994, pp. 64-65) Although some indigenous teachers working in Western schools organize their classrooms to support horizontal interactions, for others, their acculturation in mainstream pedagogy may result in directive, hierarchical organization (Barnhardt, 1981;Erickson & Mohatt, 1982;Lipka, 1991Lipka, , 1998.…”
Section: Participation Structurementioning
confidence: 99%
“…Greater success teaching Inuit students in Qallunaat schools is not unproblematic, as increased assimilation and loss of culture may result (Darder, 1991;Doige, 1999;Ogbu, 1992). Culturebased schooling may be imperative for cultural survival (Lipka, 1991;Simon, 1996;Stairs, 1994). Authentic community involvement in determining the aims of schooling is needed (Berger, 2001;Epp, & Moeller, in press), and the colonial history/present of schooling in the Canadian Arctic must inform considerations of formal education in Nunavut.…”
Section: Adaptations Of Eurocanadian Schools To Inuit Culture In Selementioning
confidence: 99%